Sounds of the Underground : A Cultural, Political and Aesthetic Mapping of Underground and Fringe Music - Graham, Stephen (Musicologist) (Book collections on Project MUSE., 2016)
In this book, Stephen Graham examines the largely unexplored terrain of underground music-exploratory forms of music-making, such as noise, free improvisation, and extreme metal, that exist outside or on the fringes of mainstream culture, generally independent from both the market and from traditional high-art institutions. Until now there has been little scholarly discussion of underground music and its cultural, political, and aesthetic importance. In addition to providing a much-needed historical outline of this diverse scene, Stephen Graham focuses on the digital age, showing the underground and its fringes as based largely in radical anti-capitalist politics and aesthetics, tied to the political contexts and structures of late-capitalism. Sounds of the Underground explores these various ideas of separation and capture through interviews and analysis, developing a critical account of both the music and its political and cultural economy.